Linked data in ECU digital collections - Dragon, Patricia M. (My University, 2019)
Presentation given as part of a panel entitled Linked Data Experiments in North Carolina Libraries, at the North Carolina Library Association Biennial Conference, Winston-Salem, N.C., 2019.
Keywords: linked data, metadata, digital collections, authority control